Možnost uporabe vprašalnika za oceno funkcijskih sposobnosti pri načrtovanju aktivnosti zdravstvene nege otrok s cerebralno paralizo - Osolnik, Sabina (Rehabilitacija (Ljubljana), 2014)
Background: A child with cerebral palsy (CP) is characterized by a reduced ability to maintain posture, to move, to process sensory information and quite frequently to have feeding, speech, behaviour and cognitive problems. Besides the gross motor function professionals are interested in functioning in different domains, such as selfcare and social skills. The Paediatric evaluation of disability inventory (PEDI) is valid instrument for evaluation of these domains in all chronically ill children. We wanted to know whether nurses could use PEDI for care planning. We also anticipated that the children in higher gross motor function classification system (GMFCS) levels would show more difficulties in self-care and social skills domains of PEDI, which could also be used as predictor for nursing care needed at the department. Methods: We reviewed the records of 100 children with CP, who were referred to the children's department of the University Rehabilitation Institute of Republic Slovenia. We collected data on age, gender, GMFCS level and results of PEDI and analysed the correlation between the level of GMFCS and the results of the individual subscales of the PEDI. Further we compared the content of the PEDI questionnaire with a list of the basic life skills that nurses use to plan their work. Results: One hundred children with CP were included in the study, 53 boys and 47 girls with an average age of 3.3 years (SD 1.32) at first admission. From the available documentation we have gathered the PEDI results for 62 children. The analysis showed that the results of all PEDI subscales were significantly in correlation with the GMFCS level (p <0.01). Comparison of the list of basic life skills, which is used by nurses, and skills in the PEDI showed that they overlap perfectly. Conclusion: The achievements of children with cerebral palsy on each subscale PEDI were significantly associated with the level of GMFCS. The questionnaire PEDI could become an integral part of the documentation of nurses since it includes all the basic life skills needed to be evaluated in the process of planning and implementation of nursing care.
Keywords: assessment; Cerebral Palsy; cerebralna paraliza; Child; družina; Family; Nursing Care; ocenjevanje; otroci; PEDI; rehabilitacija; Rehabilitation; vocational rehabilitation; zdravstvena nega